The Effect of Inflation and Minimum Wages on Labor Absorption in Indonesia for the 2013-2023 Period - Vingky, Vingky Dwi Pratama; Marsanda Hutagalung; Zulfa ‘Afifah; Tasya Manurung; Muhammad Yusuf (International Journal of Advanced Research, 2024)
This research aims to determine the effect of inflation and minimum wages on labor absorption in Indonesia for the 2013-2023 period. The method used is quantitative descriptive, namely numerical data in the form of numbers and then processed using the eviews application. The data used in this research is secondary data, namely data obtained from BPS, BI, and so on. The data analysis technique in this research uses multiple linear regression analysis hypothesis testing and classical assumptions which include normality tests and multicollinearity tests. The research results show that simultaneously the inflation and minimum wage variables have a positive and significant influence on the labor absorption variable in Indonesia. Meanwhile, partially the inflation variable has a negative and significant influence on the labor absorption variable in Indonesia and the minimum wage variable has a positive and significant influence on the labor absorption variable in Indonesia.